2014
DOI: 10.1016/j.epsl.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Clumped fluoride-hydroxyl defects in forsterite: Implications for the upper-mantle

Abstract: The mechanism and magnitude of fluorine incorporation in H-bearing forsterite were investigated through a combined experimental and theoretical approach. Forsterite samples were synthesized in a piston cylinder press at 2 and GPa, in hydrous conditions, with or without fluorine. High fluorine solubilities of 1715 and 1308 ppm F were measured by particle induced gamma-ray emission (PIGE) in forsterites synthesized at 2 and 4 GPa, respectively. In addition, first-principles calculations based on density function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 56 publications
(81 reference statements)
7
35
0
Order By: Relevance
“…The discrepancy between these data is perhaps due to the presence of micro-inclusions, clinohumite lamellae, or clumped OH/F defects (Crépisson et al 2014) in the high F olivine ).…”
Section: F and CL Partition Coefficients For Hydrous Experimentsmentioning
confidence: 49%
“…The discrepancy between these data is perhaps due to the presence of micro-inclusions, clinohumite lamellae, or clumped OH/F defects (Crépisson et al 2014) in the high F olivine ).…”
Section: F and CL Partition Coefficients For Hydrous Experimentsmentioning
confidence: 49%
“…F was measured using Particle Induced Gamma Ray Emission (PIGE) following the procedure described in Crépisson et al (2014). Hydrogen was measured using Elastic Recoil Detection Analysis (ERDA) using the procedure described in Before any analysis, the largest crystals were selected with SEM cartographies.…”
Section: Methodsmentioning
confidence: 99%
“…An additional possibility might be a competition process between OH and F for incorporation in the mineral lattices of Wd and Rw. Indeed, a recent study combining infrared characterization of experimentally F-and OH-enriched olivines and first-principle calculations, Crépisson et al (2014) have demonstrated a close association of fluoride, hydroxyl groups and Si vacancies. They found evidence for the presence of clumped fluoride-hydroxyl defects in the forsterite structure.…”
Section: Water and Fluorine In Ringwoodite And Wadseyitementioning
confidence: 98%
See 2 more Smart Citations